Give constructions across languages - Bouveret, Myriam (Constructional approaches to language ;, 2021)
"This cognitive contrastive study in ten languages (Chinese, Dalabon, English, French, Spanish, Romanian, Kurdish, Khmer, Polish, Tibetan) focuses on the verb give and its syntactic-semantic interface based on six main points, namely argument structure, lexical semantics and event structure, role marking in the three argument construction and in other constructions, lexicalization, grammaticalization and constructionalization of the verb from a cognitive construction grammar point of view (lexicon-grammar continuum), central and extended meanings. We propose that a continuum approach to grammar and lexicon is needed to describe the typological and historical facts. We argue that there is a concrete and abstract transfer 'cluster model' involving coverage of lexical and grammatical extension or bleaching phenomena and that the semantic extensions (metaphorical and otherwise) exploit various portions of this schema. This book, deeply anchored into the Cognitive Construction Grammar theoretical movement, proposes analyses of constructional phenomena which illustrate a grammar to lexicon continuum, in synchrony and diachrony: language change, grammaticalization chains, constructionalization analysis, and an invariant hypothesis of the verb give as a basic verb in human cognition"--